Inside/ Outside: From the Basics to the Practice of Design - Grear, Malcolm (USA New Riders, 2006)
This fully updated second edition of bestseller, Inside/ From the Basics to the Practice of Design, combines the practical with the philosophical and the concrete with the abstract. Deftly and sparingly capturing the essence of his subject matter. Grear offers unique insight into the design process with images and forms drawn from nature, typography, art and design. These examples from both his teaching (inside) and professional practice (outside) begin with design problems and illuminate the processes by which the best solutions are found. Grear skillfully bridges the gap between design theory and real-world practice.
Age Group: Adult
Includes index.
Keywords: Design; Graphic Arts -- Practice; Graphic arts -- Study and teaching